Mothership. - See, Rebecca Jing Hui (2014)
Mothership examines the relationship within the artist’s family. Given that the family had relocated seven times when she was growing up, she questions the idea of “home”. There was no physical space that made her feel at home. It was the family’s continuous care and support that gave her a sense of belonging. The invisible relationship that she has with her family, even though they are not physically demonstrative, is shown through the mother’s systematic and organised routines that create a bond within the family. Therefore, instead of capturing the moments, she chooses to look towards the daily routines of her family. Her mother being the dominant figure in the family is painted red, representing importance and love.